2021
DOI: 10.1186/s12884-020-03531-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antenatal care on under‐five mortality in Ethiopia: a difference‐in‐differences analysis

Abstract: Background Sub-Saharan Africa, as opposed to other regions, has the highest under-five mortality rates yet makes the least improvement in reducing under-five mortality. Despite the decline, Ethiopia is among the top ten countries contributing the most to global under-five mortalities. This article examines the impact of the number of antenatal care and the timing of first antenatal care on child health outcomes. We specifically investigated if the utilization of antenatal care services positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Women in urban regions have easier access to health facilities and maternal health intervention programs [ 21 23 ]. The makeup of the urban population in terms of wealth index, educational status, and other socioeconomic characteristics may also have a beneficial impact on the use of maternal health care services [ 24 26 ]. Research in Sub-Saharan Africa has revealed that women in urban regions utilize maternal health care more.…”
Section: Introductionmentioning
confidence: 99%
“…Women in urban regions have easier access to health facilities and maternal health intervention programs [ 21 23 ]. The makeup of the urban population in terms of wealth index, educational status, and other socioeconomic characteristics may also have a beneficial impact on the use of maternal health care services [ 24 26 ]. Research in Sub-Saharan Africa has revealed that women in urban regions utilize maternal health care more.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies in low-and middle-income countries have shown a relationship between wife beating attitude on maternal healthcare services [ 23 , 30 – 32 ]. Meanwhile, there is evidence that utilization of maternal healthcare services may influence a child's health [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DID methodology generally uses panel data to estimate the causal impact of policies or programs, although crosssectional data are also used for the same purpose. [25][26][27] For this analysis, the amount of OOP expense in the second, third, and fourth quarters of 2019 (time before mandatory lockdown) was compared to the second, third, and fourth quarters of 2020 (time after mandatory lockdown). The DID regression model is based on the following equation:…”
Section: Discussionmentioning
confidence: 99%